Visual Memory and Vocabulary Growth: The Use of Flashcards in Arabic Language Learning - Siti Dzulfirda Nivea Cholis; Syafi'i Syafi'i (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study examines the impact of flashcard use on enhancing Arabic vocabulary mastery among tenth-grade students of MAN 1 Lamongan. The research was motivated by the persistent difficulty students face in acquiring sufficient vocabulary, which limits their ability to comprehend texts, construct sentences, and express ideas effectively. Employing a quantitative approach with a quasi-experimental one-group pretest–posttest design, the study involved 33 participants. Data were collected through vocabulary tests administered before and after the intervention, during which flashcards were integrated as the main instructional tool. The findings revealed a substantial improvement in students’ performance, as the mean score increased from 43.33 in the pretest to 66.06 in the posttest. A paired-sample t-test confirmed the statistical significance of the gain at both the 5% and 1% levels. Beyond quantitative results, students also showed stronger contextual understanding and greater motivation to engage in learning. These findings highlight that flashcards are not only effective in strengthening vocabulary retention but also in fostering a more interactive and stimulating learning environment